Age-related macular degeneration (AMD) - Boyd L., Samuel (Panamá : Jaypee - Highlights Medical Publishers, 2006)
The first anatomic descriptions of the macual emerged during the latter part of the 18th century. Buzzi described the macula as tje yellow poertion of the posterior retina with a central depression that was located laterl to the optic nerve.
Table of Contents Chapter 1: Normal Anatomy Chapter 2:Screening of macular Chapter 3: Pathogy Chapter 4: Risk Factor and other
Incluye índice
Keywords: OPTICAL ANATOMY; OPTOMETRY; ENFERMEDADES DE LA RETINA